Two‐Dimensional Transition Metal Dichalcogenides Trigger Trained Immunity in Human Macrophages through Epigenetic and Metabolic Pathways. Issue 20 (18th April 2022) - Peng, Guotao; Keshavan, Sandeep; Delogu, Lucia; Shin, Yuyoung; Casiraghi, Cinzia; Fadeel, Bengt
Abstract: Trained immunity is a recently described phenomenon whereby cells of the innate immune system undergo long‐term epigenetic and/or metabolic reprogramming following a short‐term interaction with microbes or microbial products. Here, it is shown that 2D transition metal dichalcogenides (TMDs) trigger trained immunity in primary human monocyte‐derived macrophages. First, aqueous dispersions of 2D crystal formulations of MoS2 and WS2 are tested, and no cytotoxicity is found despite avid uptake of these materials by macrophages. However, when macrophages are pre‐exposed to TMDs, followed by a resting period, this causes a marked modulation of immune‐specific gene expression upon subsequent challenge with a microbial agent (i.e., bacterial lipopolysaccharides). Specifically, MoS2 triggers trained immunity through an epigenetic pathway insofar as the histone methyltransferase inhibitor methylthioadenosine reverses these effects. Furthermore, MoS2 triggers an elevation of cyclic adenosine monophosphate (cAMP) levels in macrophages and increased glycolysis is also evidenced in cells subjected to MoS2 training, pointing toward a metabolic rewiring of the cells. Importantly, it is observed that MoS2 triggers the upregulation of Mo‐dependent enzymes in macrophages, thus confirming that Mo is bioavailable in these cells. In conclusion, MoS2 is identified as a novel inducer of trained immunity. Thus, TMDs could potentially be harnessed as immunomodulatory agents. Abstract : The present study demonstrates that 2D transition metal dichalcogenides (TMDs) elicit trained immunity in primary human macrophages. Evidence is provided for a role of epigenetic and metabolic rewiring in macrophages exposed to TMDs, and MoS2 is also shown to act directly on the cAMP signaling pathway. Thus, biocompatible 2D TMDs are capable of evoking "memory" responses.